Main Qualification of Hospital Administrators - Roselina, E (KnE Social Sciences, 2018)
Population growth in Indonesia has triggered an increase in the number of hospitals. This is due to the increasing needs of health facilities in the community. The impact is an increasing need for hospital staff, including administrative staff. The aim of the study was to provide a description of the qualifications expected by the hospital against its administrative staff candidates. This research used a quantitative approach with a survey method. The research was conducted from March to April 2017. The subject of this research were the head of human resources of 22 private hospitals spread in Jabodetabek ( Jakarta, Bogor, Depok, Tangerang, Bekasi) area as users of diploma three of hospital administration program. The selection was done by purposive sampling. Data were taken in one shoot measurement from March to April 2017, using questionnaire. Statistical analysis used was univariate analysis. The results of the study showed that there are five main qualifications expected in hospital administrators based on their priority scale: first priority is communication skills (40.9%); second priority is technological skills (40.9%); third priorities are writing skills (22.7%) and information organizing skills (22.7%); and fourth priority is administrative planning skills (27.2%). Keywords: qualification, hospital administrator, skill